An evaluation of portion size estimation aids: Consumer perspectives on their effectiveness. (1st July 2017) - Faulkner, Gemma P.; Livingstone, M. Barbara E.; Pourshahidi, L. Kirsty; Spence, Michelle; Dean, Moira; O'Brien, Sinead; Gibney, Eileen R.; Wallace, Julie M.W.; McCaffrey, Tracy A.; Kerr, Maeve A.
Abstract: Objective: This qualitative study aimed to investigate consumer opinions on the usefulness of portion size estimation aids (PSEA); consumer preferences in terms of format and context for use; and the level of detail of guidance considered necessary for the effective application of PSEA. Design: Six focus groups (three to eight participants per group) were conducted to elicit views on PSEA. The discussions were recorded, transcribed verbatim and analysed by two independent researchers using a template approach. Setting: The focus groups were conducted in 2013 by an experienced moderator in various sites across the island of Ireland (three in the Republic of Ireland and three in Northern Ireland) including local leisure, community and resource centres; the home environment; and a university meeting room. Participants: General population, males (n = 17) and females (n = 15) aged 18–64 years old. Participants were recruited from both urban and rural locations representing a range of socio-economic groups. Results: The majority of participants deemed the coloured portion pots and disposable plastic cup (household measures) to be useful particularly for the estimation of amorphous cereal products (e.g. breakfast cereals). Preferences were evident for "visual" PSEA (reference objects, household measures and food packaging) rather than 'quantities and measures' such as weighing in grams or ounces. Participants stated that PS education should be concise, consistent, from a reputable source, initiated at school age and communicated innovatively e.g. mobile app or TV advertisement. Guidance in relation to gender, age and activity level was favoured over a "one size fits all" approach. Conclusions: This study identified consumer preferences and acceptance of "visual" PSEA such as portion pots/cups to estimate appropriate PS of amorphous grain foods such as breakfast cereals, pasta and rice. Concise information from a reputable source in relation to gender, age and activity level should accompany PSEA.